(untitled) (The Peerian Journal, 2025)
This article addresses an important aspect of grammatical study in the Arab heritage: "grammatical criticism." It examines the approach of Ibn Hisham al-Ansari (dead. 761 AH) in his famous book, "Mughni al-Labib ’an Kutub al-A’arib," considered one of the most prominent grammatical works of an analytical and critical nature. The article focuses on demonstrating the nature of Ibn Hisham’s distinctive critical mindset and clarifying the methodological foundations he adopted in his criticism of grammarians’ statements, based on listening, analogy, and meaning. It also presents applied examples of his criticism in various parts of the book, particularly in the chapters on two- and three-letter letters. The article adopts a descriptive and analytical approach, examining the critical terms and expressions used by Ibn Hisham, such as "there is a problem," "this is far-fetched," and "the correct thing is such-and-such." Through this, it reveals the soundness of his scholarly position and his commitment to weighing opinions based on precise criteria of reasoning and comparison. The importance of this study lies in its contribution to revealing an important methodological dimension in the Arabic language sciences. It confirms that grammar was not a rigid codification, but rather a field for rich scholarly dialogue and a space for establishing a conscious critical vision. The study concludes that Ibn Hisham represented a model of a sound grammatical mind, capable of distinguishing between opinions through strong argument, precise methodology, and profound understanding. His book, Mughni al-Labib, remains a rich source for researchers in the field of grammatical criticism and linguistic methodology.